Trends in premature avertable mortality from non-communicable diseases for 195 countries and territories, 1990–2017: a population-based study. Issue 4 (April 2020) - Martinez, Ramon; Lloyd-Sherlock, Peter; Soliz, Patricia; Ebrahim, Shah; Vega, Enrique; Ordunez, Pedro; McKee, Martin
Summary: Background: The reduction by a third of premature non-communicable disease (NCD) mortality by 2030 is the ambitious target of Sustainable Development Goal (SDG) 3.4. However, the indicator is narrowly defined, including only four major NCDs (cardiovascular diseases, cancer, diabetes, and chronic respiratory diseases) and only for people aged 30–70 years. This study focuses on premature avertable mortality from NCDs—premature deaths caused by NCDs that could be prevented through effective public policies and health interventions or amenable to high-quality health care—to assess trends at global, regional, and national levels using estimates from the Global Burden of Disease, Injuries, and Risk Factors Study (GBD) 2017. Methods: We reviewed existing lists of NCD causes of death that are either preventable through public health policies and interventions or amenable to health care to create a list of avertable NCD causes of death, which was mapped to the GBD cause list. We estimated age-standardised years of life lost (YLL) per 100 000 population due to premature avertable mortality from NCDs, avertable NCD cause clusters, and non-avertable NCD causes by sex, location, and year and reported their 95% uncertainty intervals (UIs). We examined trends in age-standardised YLL due to avertable and non-avertable NCDs, assessed the progress of premature avertable mortality from NCDs in achieving SDG 3.4, and explored specific avertable NCD cause clusters that could make a substantial contribution to overall trends in premature mortality. Findings: Globally, premature avertable mortality from NCDs for both sexes combined declined −1·3% (95% UI −1·4 to −1·2) per year, from 12 855 years (11 809 to 14 051) in 1990 to 9008 years (8329 to 9756) in 2017. However, the absolute number of avertable NCD deaths increased 49·3% (95% UI 47·3 to 52·2) from 23·1 million (22·0–24·1) deaths in 1990 to 34·5 million (33·4 to 35·6) in 2017. Premature avertable mortality from NCDs reduced in every WHO region and in most countries and territories between 1990 and 2017. Despite these reductions, only the Western Pacific and European regions and 25 countries (most of which are high-income countries) are on track to achieve SDG target 3.4. Since 2017, there has been a global slowdown in the reduction of premature avertable mortality from NCDs. In 2017, high premature avertable mortality from NCDs was clustered in low-income and middle-income countries, mainly in the South-East Asia region, Eastern Mediterranean region, and African region. Most countries with large annual reductions in such mortality between 1990 and 2017 had achieved low levels of premature avertable mortality from NCDs by 2017. Some countries, the most populous examples being Afghanistan, the Central African Republic, Uzbekistan, Haiti, Mongolia, Turkmenistan, Pakistan, Ukraine, Laos, and Egypt, reported both an upward trend and high levels of premature avertable mortality from NCDs. Cardiovascular diseases, cancers, and chronic respiratory diseases have been the main drivers of the global and regional reduction in premature avertable mortality from NCDs, whereas premature mortality from substance use disorders, chronic kidney disease and acute glomerulonephritis, and diabetes have been increasing. Interpretation: Worldwide, there has been a substantial reduction in premature avertable mortality from NCDs, but progress has been uneven across populations. Countries vary substantially in current levels and trends and, hence, the extent to which they are on track to achieve SDG 3.4. By accounting for premature avertable mortality while avoiding arbitrary age cutoffs, premature avertable mortality from NCDs is a robust, comprehensive, and actionable indicator for quantifying and monitoring global and national progress towards NCD prevention and control. Funding: None.